Dampak Hukum Perjanjian Kerjasama Pemerintah Daerah Dan PT. Blue Bay Divers Terhadap Pengelolaan Pulau Saronde - Hatu, Mohamad Akbar R; Dungga, Weny Almovarid; Mustika, Waode (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
Saronde Island is administratively included in Ponelo Islands District, North Gorontalo Regency. The management of Saronde Island was previously carried out by PT Gorontalo Alam Bahari since 2013, then transferred to PT Blue Bay Divers through a new five-year cooperation. An evaluation of the agreement is needed to review the results and losses incurred. This study aims to determine the impact of the agreement between the Regional Government and PT Blue Bay Divers on the management of Saronde Island and analyse the legal consequences in the event of losses. This research uses empirical law research method and qualitative approach. The results show that the agreement has fulfilled the legal requirements, with the agreement of both parties, proven by the signing of the contract. The cooperation has a positive impact, such as increased development on Saronde Island, foreign tourist visits, local revenue, and environmental preservation. The negative impact is the lack of contribution to economic growth and empowerment of local communities. The research found that management by BBD has not fulfilled justice and benefits for local communities. The unilateral termination of the previous cooperation with PT Gorontalo Alam Bahari that was not in accordance with the Memorandum of Understanding became a weak point. The Regional Government is considered not to have suffered financial losses, but legally, the policies taken must prioritise the welfare of the people. Therefore, it is important to review the government's decision, improve community involvement in the economic ecosystem, and ensure fairness in the implementation of this cooperation. This research recommends the establishment of local regulations as a legal umbrella to protect cooperation with third parties, ensure supervision of the implementation of agreements, and encourage cooperation that is oriented towards the welfare of local communities for sustainable and inclusive development for all stakeholders.